2000
DOI: 10.1029/1999jd900993
|View full text |Cite
|
Sign up to set email alerts
|

FORTE observations of simultaneous VHF and optical emissions from lightning: Basic phenomenology

Abstract: Abstract. Preliminary observations of simultaneous VHF and optical emissions from lightning as seen by the Fast on-Orbit Recording of Transient Events (FORTE) spacecraft are presented. VHF/optical waveform pairs are routinely collected both as individual lightning events and as sequences of events associated with cloud-to-ground (CG) and intracloud (IC) flashes. CG pulses can be distinguished from IC pulses on the basis of the properties of the VHF and optical waveforms but mostly on the basis of the associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
122
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(128 citation statements)
references
References 30 publications
5
122
1
Order By: Relevance
“…Further observations on NBEs and their associated VHF TIPPs were presented in publications based on FORTE (Jacobson, 2003a, b;Jacobson and Light, 2003;) and on LASA Jacobson et al, 2007;Suszcynsky and Heavner, 2003;Wiens et al, 2008). Recently it has been shown that the VHF pulse in the TIPP associated with NBEs is neither polarized nor coherent (Jacobson et al, 2011).…”
Section: A R Jacobson and T E L Light: Revisiting "Narrow Bipolamentioning
confidence: 96%
See 3 more Smart Citations
“…Further observations on NBEs and their associated VHF TIPPs were presented in publications based on FORTE (Jacobson, 2003a, b;Jacobson and Light, 2003;) and on LASA Jacobson et al, 2007;Suszcynsky and Heavner, 2003;Wiens et al, 2008). Recently it has been shown that the VHF pulse in the TIPP associated with NBEs is neither polarized nor coherent (Jacobson et al, 2011).…”
Section: A R Jacobson and T E L Light: Revisiting "Narrow Bipolamentioning
confidence: 96%
“…This ground-truth campaign allowed 392 A. R. Jacobson and T. E. L. Light: Revisiting "Narrow Bipolar Event" intracloud lightning the unambiguous identification of radio signatures that are characteristic of various stroke types (positive and negative cloud-to-ground, or +CG and −CG; intracloud, or IC; etc.). This ground-truthing by NLDN allowed development of a rudimentary identification of stroke type from the FORTErecorded radio waveform alone (Suszcynsky et al, 2000).…”
Section: Data Resources For This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…A combination of an ELF electrical/magnetic detection with another type (most obviously an optical sensor, but possibly gamma ray, or even VHF radio) would be much more compelling (as performed on FORTE and C/NOFS at Earth-see, e.g., Fig. 5) and Suszcynsky et al 2000. As noted by Russell (2011), a low circular polar orbit is desirable for radar mapping, and a modest lightning instrument would be a valuable but relatively inexpensive augmentation to a radar mapping mission.…”
Section: Conclusion and Recommendations For Future Surveysmentioning
confidence: 99%